2003
DOI: 10.1210/jc.2003-031006
|View full text |Cite
|
Sign up to set email alerts
|

Intramyocellular Lipid Changes in Men and Women during Aerobic Exercise: A 1H-Magnetic Resonance Spectroscopy Study

Abstract: This study was designed to compare intramyocellular lipid (IMCL) changes during 60 min of submaximal exercise in men and women. Eighteen moderately active (18-38 yr) men (n = 9) and women (n = 9) were recruited. Maximum oxygen consumption (O(2)max) and body composition were used to match subjects for aerobic fitness and body composition. Subjects performed cycle ergometry for 1 h at 65% of O(2)max. Expired gases were collected throughout exercise to determine caloric expenditure and substrate use. Blood sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 34 publications
5
63
2
1
Order By: Relevance
“…However, preliminary results suggested a considerable short-term benefit from troglitazone on diabetes prevention (26), and the TRIPOD study, involving women with previous gestational diabetes who were treated with troglitazone, demonstrated a reduced incidence of diabetes (4). Other studies have shown that exercise and weight loss reduce IMCL (10,30), and our data in this study demonstrated no effects of metformin on IMCL. Therefore, it is likely that measures directed at reduction of IMCL, such as lifestyle changes and lipid diversion with thiazolidinediones, are more effective at reducing lipotoxicity and therefore more valuable in the treatment of IGT and the prevention of T2DM.…”
Section: Discussionsupporting
confidence: 43%
“…However, preliminary results suggested a considerable short-term benefit from troglitazone on diabetes prevention (26), and the TRIPOD study, involving women with previous gestational diabetes who were treated with troglitazone, demonstrated a reduced incidence of diabetes (4). Other studies have shown that exercise and weight loss reduce IMCL (10,30), and our data in this study demonstrated no effects of metformin on IMCL. Therefore, it is likely that measures directed at reduction of IMCL, such as lifestyle changes and lipid diversion with thiazolidinediones, are more effective at reducing lipotoxicity and therefore more valuable in the treatment of IGT and the prevention of T2DM.…”
Section: Discussionsupporting
confidence: 43%
“…IMCLs have been previously associated with aerobic metabolism, 6,16 and they reportedly decrease post exercise. [39][40][41] From these observations, we speculated that IMCLs decrease in response to continuous eccentric contraction if the deformity has occurred earlier than the functional loss of the Mm. Consequently, we surmised that spinal deformity can be a result of Mm dysfunction in subjects with CLBP before structural deformities develop.…”
Section: Discussionmentioning
confidence: 99%
“…After acute exercise at moderate intensity, most studies report not only a decrease in IMCL in healthy and sedentary subjects (Bucher et al, 2014;Decombaz et al, 2001;Egger et al, 2013;SchrauwenHinderling et al, 2003a;White et al, 2003) but also in endurancetrained athletes (Brechtel et al, 2001b;De Bock et al, 2007;Decombaz et al, 2001;Johnson et al, 2003;Krssak et al, 2000;Rico-Sanz et al, 2000;van Loon et al, 2003a;van Loon et al, 2003b;Vermathen et al, 2012;Zehnder et al, 2005). Importantly, the utilization of IMCL during exercise depends upon the duration and intensity of exercise and the training status of the participant.…”
Section: Effects Of Acute Exercise On Imclmentioning
confidence: 99%